Improving English Vocabulary through Artificial Intelligence (AI) Chatbot Application - Oktadela, Resy; Elida, Yusti; Ismail, Syofianis (Journal of English Language and Education, 2023)
This study aim to use of Artificial Intelligence (AI) chatbots in improving the vocabulary of students at SD-IT Iman Syafei Pekanbaru. The purpose of this training is to cultivate and develop the interest and creativity of trainees in English by enriching English vocabulary, it is a chatbot application that can be used to send digital messages in English.The purpose of this activity is to increase the vocabulary of participants to be able to communicate well in English; provide procedural explanations of the use of AI chatbot applications regarding the use of technology in English language learning and how to practice it through android applications; facilitate participants with independent learning. Furthermore, this activity also hones participants' skills to create and convey ideas in communicating in writing in English. This activity is carried out through lecture and demonstration methods. Then proceed with handsonpractice. Demonstration methods and examples involve more about deciphering and demonstrating something through examples or in other words learning by doing or learning bypractice which emphasizes learning by doing, so it's not just theory. So, trainees are given the opportunity to practice using AI chatbots Application. In addition, students make a short writing for English conversation with the help of the service team and students involved in this activity. The results of this training show that all participants are enthusiastic, happy, and motivated because this application is still unfamiliar to participants. Participants also know the use of this application, so they can indirectly learn independently whenever and wherever participants.